Web of whispers ; Task force PACC ; The other side of Pangasinan [videorecording] - Lazaro, Cheche; Ortigas, Marga; Valdellon, Nessa; Valdez, Luchi Cruz (The Probe Team, 1995)
Probes deeper into the Vizconde case ; examines the PACC and its three years track record ; a tour to Pangasinan.